Factors influencing communication between the patient diagnosed with cancer of the breast and the professional nurse - Paterson, Lesley Alison (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MCur (Nursing Science))--University of Stellenbosch, 2009.